Struktur dan Komposisi Jenis Agroforestry Kebun-Campuran pada Berbagai Luas Pemilikan Lahan Di Desa Pattalikang Kecamatan Manuju Kabupaten Gowa - Syamsuddin Millang (Biocelebes, 2009)
This research aimed to determine pattern of agroforestry system and agroforestry spesies’s structure and composition of mixed garden practiced by farmer community at various land tenure area. This research was conducted in October to December 2005 in village of Pattalikang, district of Manuju, Regency of Gowa. It was decided to establish four categories of land tenure area based on the preliminary survey and field orientation namely > 0.5 ha, 0.5-1.5 ha, 1.1-1.5 ha, and < 1.5 ha. Method used to set up those categories was Purposive Sampling in which there were 10 plots established for measurement in each type of land tenure area. The size of plot was 20 x 50 m or 0.1 ha. Tree height was measured and species name was recorded to identify the structure and composition of plant species. Herbarium was made for those plant species that have not identified. The research showed that pattern of agroforestry practiced by farmer community was agrisilviculture with irregular plant pattern. Structure and species composition of mixed agroforestry garden at different land tenure area was relatively similar one of each other. The vertical structure consisted of 3 stratum while the species composition were 28 species at land tenure area of < 0.5 ha, 25 species at land tenure area of 0.5-1.0 ha, 26 species at land tenure area of 1.0 ha -1, 5 ha, and 25 species at land tenure area of > 1, 5 ha.